Puro ódio - Delaborde, Jonas 1981-; Delaborde, Jonas 1981-; Hegray, Hendrik 1981-; Hegray, Hendrik 1981-; Sobac, Romaric; Nnoir, Ada; Noël, Jacques 1946-2016; Prigent, Stéphane 1968-; Hotu (Paraguay, 2016)
Radically moving away from their previous logic of designing a counter culture anthology, Jonas Delaborde and Hendrik Hegray, both authors of Nazi Knife from the start, present in this new publication, edited by Paraguay, a dozen iconographic sequences, assembled as to build a mega structure with multiple entrances, all congested. Each insular ensemble answers to its own mechanics, but they’re all parts of the same mental dusty palace
Offsetdruck. - Titelangaben vom Buchrücken. - Umschlag: farbig. - Auflage 1000 Exemplare
Keywords: Graphzine